(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
When a bruise develops, blood vessels are torn, blood escapes into the injured area, and there is an ensuing inflammatory reaction. Initially, the bruise appears red due to vasodilatation resulting from the inflammatory response to the trauma and extravasation of oxygenated blood. Later, interstitial deoxygenation of blood results in change of colour to blue or purple. The inflammatory response attracts macrophages that breakdown haemoglobin into biliverdin, which has a green appearance. During this process, some of the iron released combines with ferritin resulting in the formation of haemosiderin, which is brown in colour. Finally, a yellow colour is seen during the healing process which is attributed to the biliverdin being broken to bilirubin. Traditional forensic medicine textbooks in India document the formation of ‘haematoidin’ as one of the degradation products, but literature search does not prove this claim.